Evaluation of growth and production of zucchini under irrigation with brackish water - Putti, Fernando Ferrari [UNESP]; DA SILVA, Alexsandro Oliveira; Silva Junior, Josué Ferreira; Filho, Luís Roberto Almeida Gabriel [UNESP]; Klar, E Antonio Evaldo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
In view of the new environmental policies and the adaptation of agriculture to the reuse of natural resources used, the use of inferior water is now an important alternative source for irrigation in world agriculture. In order to evaluate the use of brackish water in zucchini culture, an experiment was carried out in São Paulo State, Brazil (22º 51 'S. and 48º 26' W). The experimental design was a completely randomized block with 5 levels of salinity water (ECw: 0; 1.25; 2.5; 3.75; 5 dS m-1 ) and with 5 replicates. Growth parameters were evaluated: stem length, stem diameter, root length plus and production variables: fresh stem, shoot and root matter. According to the results, the fresh stem mass presented increase of 0.48 g plant-1 for each unit increase of ECw. For the productive parameters of zucchini crop, it was observed that the salinity factor influenced the variable weight and fruit diameter (p <0.05). In the analyzed parameters, zucchini crop was tolerant to ECw greater than 2 dS m-1 without impairing its yields.
Crescimento e produção da abobrinha sob irrigação com água salobra
Keywords: Electrical conductivity; Salinity; Water reuse